STRATEGI PENINGKATAN KEMAMPUAN NUMERASI BERBASIS PROGRAM PEMBIASAAN DI SEKOLAH DASAR - Dwi Retno Sriwahyuni; Ida Dwijayanti; Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Numeracy is the ability to apply number concepts and counting skills in everyday life. Based on the results of the Minimum Competency Assessment (AKM) as captured in the education report card, it appears that most primary schools in Sulang sub-district have low numeracy levels. The purpose of writing this article is to analyze the need for a numeracy habituation program and its implementation in primary schools. This study used a qualitative descriptive research method. The data was collected through a questionnaire distributed to 3 elementary schools in Sulang sub-district targeting principals, teachers, and students as respondents. The results of the questionnaire state that the low numeracy skills of students are caused by low student interest in mathematics, therefore a comprehensive program is needed to overcome these problems, based on the results of the questionnaire stated that the solution and follow-up to improve numeracy skills can be done through a numeracy habituation program. The numeracy habituation program for students is through an additional lesson hour program. While the numeracy habituation program for teachers is through learning community activities and Teacher Working Groups (KKG). In implementing the numeracy habituation program, of course, there are supporting factors, including the enthusiasm and enthusiasm of teachers as well as the support and high commitment of the principal in running the program. Meanwhile, the inhibiting factors are inadequate facilities and infrastructure and lack of support from parents. Efforts made to overcome obstacles in implementing the numeracy habituation program are improving facilities and infrastructure, providing varied learning resources and increasing parental support through socialization of numeracy learning.